1986
DOI: 10.1152/ajpheart.1986.251.2.h357
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical control of initial lymphatic contractile behavior in bat's wing

Abstract: The initial lymphatics of the bat's wing demonstrate spontaneous rhythmical contractions that contribute to the active formation of lymph. In the present study, modulation of lymphatic activity by mechanical factors was examined. Oil was injected to block the outflow tract of individual initial lymphatic bulbs to create a state of near isovolumetric contraction. Pulse pressure, base-line pressure, and contractile frequency were measured with the servo-null technique, while base-line pressure within the bulb wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
2
18
1
Order By: Relevance
“…Our conclusion is consistent with previous studies (3,14,15) of rat mesenteric lymphatics, where calculated pump output was maintained over a pressure range from 1 to 5 cmH 2 O because increases in contraction FREQ counterbalanced decreases in SV; likewise, measurements of SV, EF, and/or flow from bovine and ovine lymphatics suggest that optimal EDP in those vessels is between 2 and 8 cmH 2 O (12,14,15,22,24,26,28,34). An upper end of 8 cmH 2 O is likely to correlate with the diminished pump capacity observed in human peripheral lymphatic vessels during chronic lymphedema (31).…”
Section: Comparison With Previous Lymphatic Studiessupporting
confidence: 92%
See 2 more Smart Citations
“…Our conclusion is consistent with previous studies (3,14,15) of rat mesenteric lymphatics, where calculated pump output was maintained over a pressure range from 1 to 5 cmH 2 O because increases in contraction FREQ counterbalanced decreases in SV; likewise, measurements of SV, EF, and/or flow from bovine and ovine lymphatics suggest that optimal EDP in those vessels is between 2 and 8 cmH 2 O (12,14,15,22,24,26,28,34). An upper end of 8 cmH 2 O is likely to correlate with the diminished pump capacity observed in human peripheral lymphatic vessels during chronic lymphedema (31).…”
Section: Comparison With Previous Lymphatic Studiessupporting
confidence: 92%
“…Preload accommodation at low volumes/pressures would allow the vessel to pump at suboptimal filling pressures that otherwise might severely compromise SV and output. Such low volumes/pressures normally may be associated with low hydration states in which lymphatic filling is minimal (24). This adaptation may be particularly relevant in peripheral lymphatic vessels subjected to gravitational loads, i.e., relatively high levels of afterload (32).…”
Section: Comparison Of the Effects Of Preload And Afterload On The Hementioning
confidence: 99%
See 1 more Smart Citation
“…Such cyclic pressure gradient variation was first shown by Hogan (196,197), who found that the pressure in the lumen of contracting initial lymph bulbs of bat wings fell below P if in diastole. In light of the fact that these initial lymphatics are contractile (199), one might argue this is a specific phenomenon for bat wings, but similar cyclic gradients have later been demonstrated for thoracic tissues (302, 315, 316) (FIGURE 8), suggesting that this may be a general mechanism, at least in organs where lymphatics are regularly exposed to external forces and pulsations resulting in contraction/compression and relaxation cycles. For this mechanism to work, it requires that the initial lymphatic vessels do not collapse in spite of the pressure gradient, and it seems generally accepted that such support is provided by the anchoring filaments (24,25,376).…”
Section: Translymphatic Transportmentioning
confidence: 61%
“…7,42 Extending the cardiac pump analogy, the intrinsic lymph pump can be modulated via inotropic (i.e., changes in the strength of contraction) and=or chronotropic (i.e., mediated by changes in the contraction frequency) fashions and physical, neural, and humoral influences. 4,6,25,39,50,56,63,65,67,[90][91][92][93][94][95][96][97][98] Our laboratory group has focused much of our efforts analyzing the physical effects of stretch and shear on the intrinsic lymph pump and other contractile mechanisms. Elevated lymph pressure acting via an increase in the stretch of the lymphatic vessel is a classic activator of the lymph pump.…”
Section: Lymphatic Contractility and The Intrinsic Lymph Pumpmentioning
confidence: 99%